The Role of Work Motivation, Information Technology And Services Quality Against Account Officer Performance in Banking - Hendarti , Yanita (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
To produce quality human resources, the organization must also be qualified. Therefore there must be improvement of organizational components. Employees in the Account Officer section are one component of the banking organization. As one of the organizational components, Account Officers are required to develop themselves and optimize their professionalism sufficiently to improve their performance. This study aims to analyze the relationship between work motivation, information technology, and service quality on the performance of Account Officers in the banking sector. These variables were selected as independent variables in this study with the aim of exploring theoretical understanding and previous findings related to Account Officer performance. The method of writing scientific articles is the method of literature study or library research. Reviewing theories and reviewing literature books that are in accordance with the theories discussed, especially the scope of human resource management (HRM). Besides that, it also analyzes reputable scientific articles and journals. All scientific articles are sourced from Google Scholar. The findings obtained are that work motivation has a positive and significant effect on the performance of Account Officers in banking, the use of information technology has a non-significant positive effect on the performance of Account Officers in banking and service quality has no direct effect on the performance of Account Officers in banking.